2009
DOI: 10.1111/j.1365-2486.2009.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐related differences in the dominance of submerged macrophytes in shallow lakes

Abstract: It has been suggested that shallow lakes in warm climates have a higher probability of being turbid, rather than macrophyte dominated, compared with lakes in cooler climates, but little field evidence exists to evaluate this hypothesis. We analyzed data from 782 lake years in different climate zones in North America, South America, and Europe. We tested if systematic differences exist in the relationship between the abundance of submerged macrophytes and environmental factors such as lake depth and nutrient le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 47 publications
6
98
2
1
Order By: Relevance
“…This may indicate that growing conditions are still not good enough and in that case transplanting will be unsuccessful. For macrophytes to maintain a clear water state a minimum coverage of the lake seems to be required; as a rule of thumb 30% coverage has been used as a minimum threshold (Jeppesen et al, 1994;Van Nes et al, 2002;Janse et al, 2008;Kosten et al, 2009a), which is in the range of 10%-40% reported by Sondergaard et al (2010), but others report the need for higher coverage (50% Tatrai et al, 2009, 60% Blindow et al, 2002. In warm lakes in tropical and subtropical regions, a higher coverage of macrophytes may be needed as the grazing of zooplankton on phytoplankton is low due to high fish predation Kosten et al, 2009a).…”
Section: Restoration Measuresmentioning
confidence: 99%
“…This may indicate that growing conditions are still not good enough and in that case transplanting will be unsuccessful. For macrophytes to maintain a clear water state a minimum coverage of the lake seems to be required; as a rule of thumb 30% coverage has been used as a minimum threshold (Jeppesen et al, 1994;Van Nes et al, 2002;Janse et al, 2008;Kosten et al, 2009a), which is in the range of 10%-40% reported by Sondergaard et al (2010), but others report the need for higher coverage (50% Tatrai et al, 2009, 60% Blindow et al, 2002. In warm lakes in tropical and subtropical regions, a higher coverage of macrophytes may be needed as the grazing of zooplankton on phytoplankton is low due to high fish predation Kosten et al, 2009a).…”
Section: Restoration Measuresmentioning
confidence: 99%
“…Macrophytes are key components in the ecological functioning of shallow lake ecosystems and they are affected by warming in various ways (Kosten et al, 2009). At the level of the plant individual, warming may affect plant physiology (Madsen and Brix, 1997;Rooney and Kalff, 2000), growth (Haag and Gorham, 1977;Short and Neckles, 1999) and reproduction (Van Vierssen et al, 1984;Mckee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophyte biomass is one of the most important indices of the ecological status of lakes (Kosten et al, 2009). High values of biomass, especially of submerged macrophytes, indicate good condition of lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Submerged ones however, particularly in shallow lakes, are sensitive to changes in habitat conditions and can change within a few years (Rooney, Kalff, & Habel, 2003;Schaumburg et al, 2004). Changes in environmental conditions including differences in nutrients and seasonal temperature can influence the composition of submerged macrophytes (Kosten et al, 2009). Nevertheless, other important factors that influence macrophyte development include wind, water level fluctuations, and algal blooms (Lechmann & Lachavanne, 1999).…”
Section: Impact Of the Drainage System On Water Vegetation Of The Lowmentioning
confidence: 99%